2013
DOI: 10.1016/j.cemconcomp.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbonation of calcareous composites: Influence of mix design

Abstract: This work combined compression moulding with subsequent super-critical carbonation treatment (100 bar, 60°C, 24 h) to fabricate cement and/or lime based ceramic composites with various aggregates. Composites were examined using mechanical testing, XRD, He pycnometry and thin-section petrography. Composites with lime-only binders were significantly weaker than those with cement-lime binders regardless of the degree of carbonation. Flexural strengths in excess of 10 MPa were routinely achieved in large (>100 mm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Early carbonation contributes to decrease these voids around the cellulose fibers. Farahi et al [35,36] also observed very little porosity at the interface between aggregate particles and groundmass when composites were submitted to supercritical carbonation. Santos et al [25] observed changes in the nanostructure in the vicinity of the fiber by energy-dispersive X-ray spectroscopy maps in extruded cement-based composite after early supercritical carbonation and before accelerated aging.…”
Section: Resultsmentioning
confidence: 89%
“…Early carbonation contributes to decrease these voids around the cellulose fibers. Farahi et al [35,36] also observed very little porosity at the interface between aggregate particles and groundmass when composites were submitted to supercritical carbonation. Santos et al [25] observed changes in the nanostructure in the vicinity of the fiber by energy-dispersive X-ray spectroscopy maps in extruded cement-based composite after early supercritical carbonation and before accelerated aging.…”
Section: Resultsmentioning
confidence: 89%
“…It seems that, in early hydration stages, the C-S-H becomes intermingled with carbonates, generating an amorphous calcium-silicatehydrocarbonate binding phase [116], while CH is converted to CaCO3 [109]. In fact, effects responsible for marked strength gain probably include subtle changes in C-S-H microstructure, not only simple pore filling by CaCO3 as often stated [121,122].…”
Section: Accelerated Carbonation Curingmentioning
confidence: 99%
“…More complex technologies such as a flow-through reactor [105] and supercritical carbonation [121,122] were also proposed.…”
Section: Accelerated Carbonation Curingmentioning
confidence: 99%
“…Here, as opposed to the short-period 3 bar CO 2 curing, carbonation continues concurrently with cement hydration in 20% CO 2 curing. Calcite crystals produced by the carbonation put C–S–H on themselves at nano-scale, and the C–S–H layer is consequently reinforced by the distributed calcite [ 35 , 36 , 37 ]. The continuous 20% CO 2 curing consequently improves the strength of the mortar sample.…”
Section: Discussionmentioning
confidence: 99%